Life after cold death: reef coral and coral reef responses to the 2010 cold water anomaly in the Florida Keys - Dustin W. Kemp; Michael A. Colella; Lucy A. Bartlett; Rob R. Ruzicka; James W. Porter; William K. Fitt (Ecosphere, 2016)
Abstract Organismal and community‐wide responses of reef‐building corals are documented before and after a severe cold‐water thermal anomaly that occurred in 2010 in the Florida Keys, USA. In January 2010 seawater temperatures dropped far below the normal minima (to <11°C), resulting in the largest documented coral mass mortality event ever recorded in the Florida Keys. Physiological measurements demonstrated species‐specific thermal sensitivities to this environmental perturbation. Four common corals with narrow thermal tolerance, Acropora cervicornis, Orbicella annularis, O. faveolata, and Porites astreoides, sustained high mortality (>80%) on inshore reefs. In contrast, another common coral with a wide thermal tolerance, Siderastrea siderea, was not affected by this cold anomaly. We measured biomass, symbiotic algal densities (genus: Symbiodinium), chlorophyll a content, and maximum quantum efficiency of photosystem II for reef‐building corals on a seasonal basis before and after the 2010 cold anomaly. Our data document a clear correspondence between physiological response, biomass levels, and survivorship among these five scleractinian coral species. These physiological findings are mirrored by in‐shore benthic community monitoring data, which show the dramatic loss of the three cold‐sensitive species and continued survival of the cold‐tolerant species. Finally, we document recruitment and survival rates of newly settled reef‐building corals on four inshore reefs, which experienced high coral mortality during the 2010 cold‐kill. Interestingly, both a cold‐tolerant species, S. siderea, and a cold‐intolerant species, P. astreoides, were the most abundant species recruiting to these postdisturbance reefs.